POTENSI TOKSISITAS NEUROLOGIS VINKRISTIN PADA TUBUH YANG TERJADI PADA ANAK DENGAN LEUKEMIA LIMFOSITIK AKUT - Ni Made Intan Pertiwi; Ketut Ariawati; Rasmaya Niruri; Rini Noviyani; A.A. Raka Karsana; Mahardika Aprilia Iflahah (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2013)
Acute Lymphoblastic Leukemia (ALL) treatment are chemotherapeutic agent and bone marrow transplantation. Treatment with chemotherapeutic agent is the primary curative for leukemia. Vincristine is one of chemotherapeutic agents in ALL. Neurotoxicity is one of the toxicity caused by vincristine. The objective of this study was to find out the potential neurotoxicity of vincristine in children with ALL. Method: This study was observational design. The study was conducted at Sanglah Hospital Denpasar. Patient data was collected from May 2011- March 2013 period. Result: Seventeen patients who fit to the sample criteria were got. Of the 17 childhood with ALL who have treatment with chemotherapeutic agent based on Indonesian Protocol 2006, 3 patients showed neurotoxicity. Patients may suffered from leg pain, foot pain, and walking pain. Conclusion: There are potential neurotoxicity vincristine in children with ALL who have treatment with chemotherapeutic agent. Potential neurotoxicity can be caused by mechanism of action vincristine in microtubules.